Implementasi Tadarus Al-Qur’an Pagi Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa MA Muhammadiyah 1 Paciran - Kamil, Khumaidi; Purwanto (STAI Muhammadiyah Paciran Lamongan, 2025)
This The Qur'an is the holy book of Islam, serving as a guide to life. Reciting the Qur'an is both worship and a means of understanding its teachings. However, students often lack proper Qur'anic reading skills due to low motivation and inappropriate teaching methods. This study examines the impact of the morning Qur'an recitation (tadarus) program on improving students' reading skills at MAM 01 Paciran. The tadarus program is conducted before classes to habituate students to recite the Qur'an according to tajweed rules. Results show that the program effectively enhances reading skills through habituation, awareness, and love for the Qur'an. Students who actively recite and listen to their peers and teachers demonstrate significant improvements. Educational and family backgrounds also influence initial skills. This study provides recommendations for implementing similar programs to improve Islamic education quality.